Evaluasi Website Universitas Amikom Purwokerto - Andi Dwi Riyanto; Muliasari Pinilih; Alfiana Oktaviani; Eka Riyana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The website Amikom Purwokerto University has an important role in disseminating information, therefore it is necessary to evaluate the quality of the website. The evaluation uses the Webqual variables and Importance Performance Analysis (IPA) approaches. The respondent is lecturers and students of University Amikom Purwokerto. The level of conformity per indicator is only US4 (easy to use) getting a match rate of 100% and IQ1 (accurate information), IQ2 (trustworthy), IQ5 (easy to understand), SIQ3 (user's personal information), and SIQ4 (space for personalization for users) getting a match rate greater than 100%. Based on quadrant analysis, quadrant I only IQ6 (quite detailed information is provided). Quadrant II consists of US1 (easy to learn and operate), US2 (interaction with users is clear and easy to understand), US4 (easy to use), US6 (design according to the type of website), IQ1 (accurate information), IQ2 (trustworthy), IQ4 (relevant information), IQ5 (easy to understand), IQ7 (appropriate delivery format), and SIQ1 (good website reputation). In quadrant III there are US3 (easy to navigate), US5 (attractive appearance), US7 (good performance), US8 (providing a positive experience for users), IQ3 (up to date information), SIQ2 (feeling safe), SIQ4 (space for personalization for users), SIQ5 (gives a sense of community), SIQ6 (easy to communicate with other users), and SIQ7 (services as promised). Quadrant IV only contains SIQ3 (user's personal information).